International financial management - Eun, Cheol S. (Irwin/McGraw-Hill, 1998)
The overriding objective of the text is to teach students how to be effective global financial managers. The text covers the fundamentals of the macroeconomic environment of international financial management, discusses the financial environment in which the multinational firm and its managers must function, and covers foreign exchange management and financial management in a multinational firm.